2012
DOI: 10.1139/z2012-053
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes and consistency in male physical and behavioural traits have implications for mating success in the grey seal (Halichoerus grypus)

Abstract: We examined age-related changes and consistency in physical and behavioural traits of 20 male grey seals (Halichoerus grypus (Fabricius, 1791)) and implications for a proxy of mating success (number of oestrous females attended) over four successive breeding seasons on Sable Island, Canada. Across the study, young males (10-15 years) gained body mass, while old males (23-31 years) lost body mass. Body length was an important determinant of tenure (time spent at a site among females) and males of all ages exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“…This could be an early expression of behavioral strategies seen in adults, as an adult male's size, dominance ranking, and aggression frequencies have been linked to each other and to mating success in several phocid species (gray seals: Anderson and Fedak , Godsell , Lidgard et al . ; harbor seal: Sullivan ; southern elephant seal, Mirounga leonina : McCann , Modig ; northern elephant seal, Mirounga angustirostris : Haley et al . ).…”
Section: Model Output From the Gamm Analyzing Aggression Frequencies mentioning
confidence: 99%
See 1 more Smart Citation
“…This could be an early expression of behavioral strategies seen in adults, as an adult male's size, dominance ranking, and aggression frequencies have been linked to each other and to mating success in several phocid species (gray seals: Anderson and Fedak , Godsell , Lidgard et al . ; harbor seal: Sullivan ; southern elephant seal, Mirounga leonina : McCann , Modig ; northern elephant seal, Mirounga angustirostris : Haley et al . ).…”
Section: Model Output From the Gamm Analyzing Aggression Frequencies mentioning
confidence: 99%
“…In our study group, male weaned pups showed more aggression the larger they were compared to other individuals. This could be an early expression of behavioral strategies seen in adults, as an adult male's size, dominance ranking, and aggression frequencies have been linked to each other and to mating success in several phocid species (gray seals: Anderson and Fedak 1985, Godsell 1991, Lidgard et al 2012harbor seal: Sullivan 1982;southern elephant seal, Mirounga leonina: McCann 1981, Modig 1996; northern elephant seal, Mirounga angustirostris: Haley et al 1994). However, the males in our study were approximately 8 yr away from the age they would typically first be able to hold tenure on a breeding colony (Godsell 1991).…”
mentioning
confidence: 99%
“…Each individual strives to contribute to the future generation, but reproduction has its costs: the energy and nutrient demands of reproducing are large. Furthermore, morphological changes are needed to better meet these demands (e.g., Cockbum, 1989;Lidgard et al, 2012). In each matemity roost only between 50-90% of females participate in reproduction, because some females need a recovery year after successful reproduction (Ransome, 1995;Barclay et al, 2004).…”
Section: Trade-offs Between Reproduction Maturity and Longevitymentioning
confidence: 99%
“…Comparing morphometric measures, such as maximum body length and juvenile growth rates, can therefore assist in understanding how nutritional and food-related constraints may be impacting populations. Indeed, for pinniped species with polygynous breeding systems and large degrees of sexual dimorphism, attaining maximum body length may be particularly important for males where size is related to mating success (Lidgard, Bowen, & Boness, 2012). Indeed, for pinniped species with polygynous breeding systems and large degrees of sexual dimorphism, attaining maximum body length may be particularly important for males where size is related to mating success (Lidgard, Bowen, & Boness, 2012).…”
Section: Introductionmentioning
confidence: 99%